2021
DOI: 10.1002/jhbp.956
|View full text |Cite
|
Sign up to set email alerts
|

Survey of surgical resections for neuroendocrine liver metastases: A project study of the Japan Neuroendocrine Tumor Society (JNETS)

Abstract: Background/Purpose Hepatic resection is considered the treatment of choice for neuroendocrine liver metastases (NELM). However, the safety and efficacy of resection have not been fully evaluated using a large cohort. The aim of the present study was to collect real‐world data regarding hepatic resections for NELM. Methods A retrospective, multicenter survey was conducted. The background characteristics of patients undergoing an initial hepatic resection for NELM, the operative details, pathological findings, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The analysis of a study by the Japanese NET Society (JNETS) found that, after R0/1 resection of pNETs liver metastases, the recurrence rate of intrahepatic metastases was 63.4%. [109] Despite the high postoperative recurrence rate, a few studies have reported on its postoperative treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of a study by the Japanese NET Society (JNETS) found that, after R0/1 resection of pNETs liver metastases, the recurrence rate of intrahepatic metastases was 63.4%. [109] Despite the high postoperative recurrence rate, a few studies have reported on its postoperative treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, however, various reviews have linked NELMs resection to an improvement in symptoms and longer OS for patients with PanNETs, but this has not yielded a consensus on its overall benefits given the presence of selection bias, lack of randomized trials, and availability of other management options. Table 4 below summarizes the findings of several articles relating to resection of NELM (31)(32)(33)(34)(35)(36)(38)(39)(40)(41)(42).…”
Section: Benefits Of Surgical Resection Of Metastasesmentioning
confidence: 99%
“…One consistency throughout most studies covering surgical resection for NELMs is the high rate of metastatic recurrence observed. In their pancreatic NELMs specific review, Partelli et al document a recurrence rate of 76.5% after surgical resection while a recent multi-institutional study from Japan noted only a 13.4% 5-year recurrence-free survival rate in their surgically treated patients, 59% of which had PanNET primaries ( 34 , 38 ).…”
Section: Surgery For Resectable Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of NELM, LR is the treatment of choice whenever feasible, since patient outcomes after resection have been reported to be favorable compared to those with unresectable tumors [ 120 ]. Repeat hepatectomy, if feasible, can be a good option for intra-hepatic recurrence and can provide long-term survival [ 121 ].…”
Section: Parenchyma-sparing Vs Regenerative Liver Surgerymentioning
confidence: 99%